DIVERSIFIKASI PENDAPATAN TERHADAP PROFITABILITAS DAN RISIKO BANK DI INDONESIA SELAMA PANDEMI COVID-19 - Sudibyo Ikhsan; Hersugondo Hersugondo (Faculty of Economic and Business Universitas STIKUBANK, 2021)
Reducing the variability of their income by diversifying outside of traditional lending activities into non-interest income sources. We influence the COVID-19 pandemic on the relationship between the use of non-interest income and bank profits and risks in Indonesian banks. The economic effects of the pandemic have resulted in tightening of credit standards and reduced demand for various types of loans. We find that non-interest income sources are positively related to performance but inversely related to risk. These results are consistent with the beneficial diversification effect during the pandemic of banks expanding outside of traditional loan revenue sources. Keywords: covid-19, profitability, bank, risk